2016
DOI: 10.1002/elps.201500517
|View full text |Cite
|
Sign up to set email alerts
|

Liquid chromatography-electron ionization tandem mass spectrometry with the Direct-EI interface in the fast determination of diazepam and flunitrazepam in alcoholic beverages

Abstract: This is the first application based on electron ionization (EI) using a Direct-EI LC interface and MS/MS to detect unequivocally target compounds in a very small real sample. The determination and quantification of benzodiazepines in very small residues of beverages, collected at the scene of drug-facilitated crimes are mandatory in legal procedures. A specific and sensitive analytical instrumentation is needed, involving little or no sample preparation. Here, a direct flow injection analysis of alcoholic beve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…Addition of an in-vacuum plasma ionization source minimized ion transfer loss in the continuous atmospheric pressure interface. Another interesting coupling of techniques came from Famiglini et al These authors highlighted a direct interface of electron ionization (EI) with LC for direct flow injection-MS/MS of small molecules in alcoholic beverages. Benham et al coupled laser-induced acoustic desorption (LIAD) with APPI and demonstrated its utility by analyzing a number of low-polarity organics .…”
Section: Discharge-based Ambient Ionizationmentioning
confidence: 99%
“…Addition of an in-vacuum plasma ionization source minimized ion transfer loss in the continuous atmospheric pressure interface. Another interesting coupling of techniques came from Famiglini et al These authors highlighted a direct interface of electron ionization (EI) with LC for direct flow injection-MS/MS of small molecules in alcoholic beverages. Benham et al coupled laser-induced acoustic desorption (LIAD) with APPI and demonstrated its utility by analyzing a number of low-polarity organics .…”
Section: Discharge-based Ambient Ionizationmentioning
confidence: 99%
“…Direct-EI was successfully used in a variety of applications [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] in a range of fields of research, demonstrating the lack of matrix effects [39][40][41]. It is not influenced by the co-elution of analytes or matrix components, making it highly suitable for direct introduction of diluted samples without chromatographic separations [37] or paired with a condensed-phase membrane introduction mass spectrometry (CP-MIMS) for real time monitoring of aqueous solutions [38] through a direct analysis of co-permeating compounds. Direct-EI has been successfully used by Zimmermann and coworkers [42,43] with direct infusion resonanceenhanced multiphoton ionization (DI-REMPI) and in combination with single photon ionization (SPI) for hard and soft ionization.…”
mentioning
confidence: 99%
“…Both for the direct flow injection analysis of 16 polyaromatic hydrocarbons (PAHs) and the Direct-EI-LC-MS analysis of four hormones, peaks obtained with a ceramic coated ion source were much sharper and displayed significantly higher signal-to-noise (S/N) ratios (up to a four-fold increase) compared to a stainless-steel ion source. The application of the Direct-EI LC interface in combination with MS/MS was also demonstrated for the targeted detection and quantification of benzodiazepines in alcoholic drinks 29 . For this purpose, a fast direct-injection method requiring no prior sample preparation was proposed and validated, resulting in detection limits (LOQ) between 100 and 500 µg/L when injecting 2 µL of sample.…”
Section: Ionizationmentioning
confidence: 99%